Policy drivers of farm succession and inheritance. (February 2017) - Leonard, Brian; Kinsella, Anne; O'Donoghue, Cathal; Farrell, Maura; Mahon, Marie
Abstract: Farm succession and inheritance is increasingly considered a complex phenomenon which not only affects core dimensions of farm family life but also the agricultural sector more widely. Intergenerational farm transfer in particular is increasingly viewed as fundamental to the sustainability and development of global agriculture. In the majority of EU countries, the average age of farmers is increasing, while the number of farmers under 40 years of age is decreasing. There is growing concern that this demographic trend may have negative impacts on the agricultural industry because it is younger and not older farmers who are associated with more efficient and effective production practices. The question of what motivates decisions to transfer farms is a complex one, and research to date has not apparently enlightened agricultural policy to the extent that current trends towards an ageing farm population are being managed. This research aims to investigate economic and financial aspects of the policy drivers of farm succession and inheritance in Ireland to understand what it is about the policy environment that is failing to stimulate higher levels of farm transfer. It draws on the Teagasc National Farm Survey data which provides Irish data to the Farm Accountancy Data Network in the European Commission. A hypothetical microsimulation model is used to investigate economic factors of farm transfers, with scenarios created to test these factors and their impacts on the transfer process. The Net Present Value (NPV) of income streams for farmers and their successors are calculated to assess which scenarios have the highest/lowest financial effects. The findings illustrate a range of possible scenarios for farm succession/inheritance, with some results indicating that under current policy retaining a farm until death may be more economically beneficial to a farmer than transferring land before death.